Gene expression of Candida albicans strains isolates from patients with denture stomatitis submitted to treatments with photodynamic therapy and nystatin - Alonso, Gabriela Caroline; Klein, Marlise Inêz; Jordão, Cláudia Carolina; Carmello, Juliana Cabrini; Pavarina, Ana Cláudia (Elsevier, 2021)
The study evaluated the effect of antimicrobial photodynamic therapy (aPDT) and nystatin (NYS) in the expression of genes (ACT1, ALS1, CAP1, CAT1, EFG1, HWP1, LIP3, PLB1, SAP1, and SOD1) involved in the virulence of Candida albicans strains recovered from patients with denture stomatitis (DS). These strains were isolated from the patients before (initial) and after treatment (final), and 45 days after the treatments (follow-up). For gene expression analyses, RNA was isolated from the clinical strains, followed by cDNA synthesis and qPCR using specific primers for each target gene. The samples that present integrity were pooled to increase the RNA yield. In the end, four patients treated with aPDT and five patients treated with NYS had the clinical isolates of C. albicans submitted to gene expression evaluation. The data demonstrated a statistical difference in the expression of PLB1 and ACT1 for the different therapies (aPDT versus NYS). Also, there was a statistical difference in the expression of CAT1, SOD1, and LIP3 at the time intervals assessed (initial, final, and follow-up). In contrast, no statistical difference was found in the expression of ALS1, HWP1, EFG1, CAP1, CAT1, SOD1, LIP3, and SAP1 between the therapies, while no significant difference was detected at the time intervals evaluated for ALS1, HWP1, EFG1, CAP1, and SAP1. Therefore, the topical treatments for DS with aPDT or NYS did not effect the expression of most C. albicans virulence genes evaluated.
Keywords: Candida albicans; Gene expression; Molecular pathways; Photodynamic therapy; Virulence